Tiempos modernos : material extra = Modern Times : Special Features - Robinson, David (introducción); Robinson, David (guión); Robinson, David (conducción); Truffaut, Philippe (realización); Toubiana, Serge (edición); Truffaut, Philippe (realización); Lange, Eric (investigación); Brownlow, Kevin (asesoría); Guéneau, Olivier (fotógrafo); Andrews, Tatiana (montaje); Cortázar, Octavio (realización); Lopito (fotógrafo); et al. ((La Colección de Chaplin))
En español, francés e inglés, con subtítulos opcionales: español, chino, coreano, inglés, portugués, thai